British Paediatric Neurology Association 2018
DOI: 10.1136/archdischild-2018-rcpch.306
|View full text |Cite
|
Sign up to set email alerts
|

G315(P) Treatment of anticardiolipin antibody mediated chorea in an adolescent male

Abstract: BackgroundAnti-phospholipid antibody associated chorea is a rare cause of this movement disorder, with a higher incidence in females and children. Other causes include Wilson’s disease, Sydenham’s chorea and ataxia-telangiectasia. Aetiology is uncertain, but may involve anti-phospholipid mediated dysfunction of the basal ganglia. We report an unusual case of anticardiolipin antibody related chorea in an adolecent male presenting to secondary care services.Case reportOur patient is a 14 year old male who became… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only four studies of non-pharmacological interventions with an APS-specific sample appeared in our search, and they contained only physiological outcomes (e.g., heart rate, time-to-exhaustion, VO2 peak) rather than patient-reported outcomes. 4043 Of note, three of these four studies contained data from the same participants. 4143 We did find one study that contained patient-reported outcomes 44 and described perceptions of barriers to engaging in physical activity and exercise from the perspective of individuals with APS, 26 but it did not test a specific intervention.
Figure 1.PRISMA flow diagram.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four studies of non-pharmacological interventions with an APS-specific sample appeared in our search, and they contained only physiological outcomes (e.g., heart rate, time-to-exhaustion, VO2 peak) rather than patient-reported outcomes. 4043 Of note, three of these four studies contained data from the same participants. 4143 We did find one study that contained patient-reported outcomes 44 and described perceptions of barriers to engaging in physical activity and exercise from the perspective of individuals with APS, 26 but it did not test a specific intervention.
Figure 1.PRISMA flow diagram.
…”
Section: Resultsmentioning
confidence: 99%
“…The other APS-specific case study we identified reported involving rehabilitation professionals in the treatment of a 14-year-old male patient. 40 The treatment significantly improved his choreoathetoid movements in both upper and lower extremities, though no patient-reported outcome measures were listed. Overall, we found a dearth of evidence regarding non-pharmacological interventions and APS.…”
Section: Discussionmentioning
confidence: 96%